Validation of the patient assessment of chronic illness care (PACIC) short form scale in heart transplant recipients: the international cross-sectional bright study - Katia Iglesias; Sabina De Geest; Lut Berben; Fabienne Dobbels; Kris Denhaerynk; L. Cynthia Russell; Remon Helmy; Isabelle Peytremann-Bridevaux; on behalf of the BRIGHT study team (BMC, 2020)
Abstract Background Transplant recipients are chronically ill patients, who require lifelong follow-up to manage co-morbidities and prevent graft loss. This necessitates a system of care that is congruent with the Chronic Care Model. The eleven-item self-report Patient Assessment of Chronic Illness Care (PACIC) scale assesses whether chronic care is congruent with the Chronic Care Model, yet its validity for heart transplant patients has not been tested. Methods We tested the validity of the English version of the PACIC, and compared the similarity of the internal structure of the PACIC across English-speaking countries (USA, Canada, Australia and United Kingdom) and across six languages (French, German, Dutch, Spanish, Italian and Portuguese). This was done using data from the cross-sectional international BRIGHT study that included 1378 heart transplant patients from eleven countries across 4 continents. To test the validity of the instrument, confirmatory factor analyses to check the expected unidimensional internal structure, and relations to other variables, were performed. Results Main analyses confirmed the validity of the English PACIC version for heart transplant patients. Exploratory analyses across English-speaking countries and languages also confirmed the single factorial dimension, except in Italian and Spanish. Conclusion This scale could help healthcare providers monitor level of chronic illness management and improve transplantation care. Trial registration Clinicaltrials.gov ID: NCT01608477, first patient enrolled in March 2012, registered retrospectively: May 30, 2012.